Enterobacteriaceae resistentes a carbapenémicos aisladas en muestras de pacientes hospitalizados - Gallegos Criollo, David Alejandro (2022)
The Enterobacteriaceae family is part of the organism's microbiota, competing with other pathogenic microorganisms; they act as opportunists causing more than 50% of nosocomial infections, have a high capacity for adaptation, being located in the group of superbugs with high multi-resistance indices, due to the common administration of no controlled medication. The present work aimed to know the genes Carbapenemase Producers in Enterobacteriaceae Isolated from Patient Samples hospitalized at the Isidro Ayora Hospital, Loja; Through a descriptive-cross- sectional study, isolated 32 carbapenemase-producing Enterobacterals. The results obtained evidence that Klebsiella pneumoniae and Escherichia coli are the predominant bacteria infections among hospitalized patients; Klebsiella. pneumoniae presents higher indices of resistance; Thus, the carbapenemase-producing gene that predominates in the local area is the blaKPC